Pelatihan Pembuatan Media Pembelajaran Matematika di SD Negeri Jatimekar 02 - Sri Awan Asri; A Rahim; Ilmi Noor Rahmad (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
In general, elementary school age children (SD) are experiencing development at their thinking level, elementary school children's thinking stages are still not formal and are still concrete in nature. Therefore, the teacher must present material that is real so that elementary students can understand the concept completely. Based on the results of interviews with several mathematics teachers and principals, information was obtained that mathematics learning is carried out very rarely using media, especially in the form of props or other innovative media. Regarding the above problems, we are interested in conducting training through a community service program entitled